O uso do tempo e das práticas epistêmicas em aulas práticas de química - Angélica Oliveira de Araújo (2008)
Embedded in a tradition which takes the contributions of socio-cultural theory in the analysis of the teaching and learning processes, linking up the contributions of Vygotsky and Bakhtin, this study seeks to identify: (i) How the time is used in practical classes, by the students and the teacher (ii) the development, by students, of epistemic practice (Sandoval & Reiser, 2004, Jiménez-Aleixandre et. al. 2008) that emerge in the speech during the implementation of practical activities. We present a dynamic discursive analysis of nine practical classes held in a class of 2nd year of high school of a school's private network of the city of Belo Horizonte. In six lessons the teacher worked content related to thermal physics and introductory concepts of thermo-chemistry and in three others, the factors that affect the rates of chemical reactions. The teacher developed in these classes, experiments with students, demonstrating experiments and discussions about the practical problems they experienced. Accordingly, we analyze the epistemic practices that emerge in the speech of students, seeking to understand the discursive interactions between students and teacher and the commonly used strategies by the teacher to mediate these interactions.